2022
DOI: 10.3390/healthcare10050862
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Combined Physical and Cognitive Interventions on Direct and Indirect Fall Outcomes for the Elderly with Mild Cognitive Impairment: A Systematic Review

Abstract: This review was intended to determine the effectiveness of physical and cognitive training (PCT) on falls and fall-related factors and cognitive function among community-dwelling elderly people with mild cognitive impairment (MCI). A systematic literature search was performed of the MEDLINE, CINAHL, Web of Sciences, Scopus, ProQuest, Embase, and Google Scholar databases for articles published from 2010 to 2020. The studies that combined PCT to assess their impacts on fall outcomes both directly and indirectly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Thirdly, there is a lack of consensus on targeted outcomes. Some studies focused primarily on mobility ( Kiper et al, 2022 ; Mai Ba and Kim, 2022 ) while others focused on cognition ( Yan et al, 2022 ). Lastly, while one meta-analysis ( Meng et al, 2022 ) has synthesized clinical trials combining cognitive intervention and physical exercise on multiple cognitive domains in pwMCI, this meta-analysis excluded behavioral interventions other than physical exercise and included single intervention comparisons to study the additive effects instead of the overall impact of multimodal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, there is a lack of consensus on targeted outcomes. Some studies focused primarily on mobility ( Kiper et al, 2022 ; Mai Ba and Kim, 2022 ) while others focused on cognition ( Yan et al, 2022 ). Lastly, while one meta-analysis ( Meng et al, 2022 ) has synthesized clinical trials combining cognitive intervention and physical exercise on multiple cognitive domains in pwMCI, this meta-analysis excluded behavioral interventions other than physical exercise and included single intervention comparisons to study the additive effects instead of the overall impact of multimodal interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Only two systematic reviews were identified investigating Mild Cognitive Impairment and fall risk reduction for people living in the community. 16,17 Less than half of the studies included in these reviews actually measured falls events as an outcome measure.…”
Section: Introductionmentioning
confidence: 99%